Effects of different fat sources on performance parameters and carcass characteristics of broiler chicks - NAWAZ, HAQ; RASHEED, SHABANA; HAQ, AHSAN UL; YAQOOB, MUHAMMAD; SHAMI, MUHAMMAD MOHSAN (The Indian Journal of Animal Sciences, 2015)
An experiment was conducted to investigate the effect of feeding different sources of supplemental fat (soybean oil, poultry fat, tallow and canola oil) on the live performance and carcass characteristics of broiler chicks. Statistical analysis showed nonsignificant differences in feed intake of broiler chicks fed diets containing different sources of supplemental fat. Significantly higher weight gain and better FCR were observed in birds fed diet containing poultry fat than those fed diets containing other sources of fat. Nonsignificant differences of added dietary fat sources were observed on carcass characteristics and blood pH. From this study, it is obvious that supplemental poultry fat showed beneficial effect on live weight gain and FCR of broiler chicks.